An integrative approach to understanding vulnerability of an alpine range-restricted bird to climate warming - Oswald, Krista Natasha (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Understanding species' vulnerability to climate change requires an integrative ecological approach involving, at minimum, physiology, behaviour, reproductive success, and limitations on dispersal. In this thesis I determined potential negative effects of increasing temperatures on behaviour, reproduction, and ability to disperse in an alpine-restricted bird, the Cape Rockjumper Chaetops frenatus ("Rockjumper"). Here I provide a comprehensive ecological set of data for understanding the link between Rockjumper population declines and warming habitats. I tested whether Rockjumper microsite-use at high temperatures resulted in decreased time spent on important behaviours, such as foraging. I found Rockjumpers made increased use of rock-shade as air temperature increased and so spent less time panting, but birds in rock-shade foraged less. Birds may be constrained to foraging in sun at high temperatures to sustain energy or water requirements, despite risks of high thermal load, or else face lost foraging opportunities by remaining in rock-shade. I determined if adult nest attendance and causes of nest failure were related to high temperatures. I filmed nests over two breeding seasons to examine temperature-effects on adult time in nests, provisioning rate, and resultant nestling daily mass gain. The only temperature effect I found was decreased percent daily change in body mass for older nestlings at hotter temperatures. I also examined causes of nest failure over three breeding seasons in relation to nest concealment and habitat openness by observing failure/success. Nests in more open territories (i.e. early post-fire habitat) had greater success, and the main cause of predation came from Boomslang Dispholydus typus. Importantly, the probability of Boomslang predation increased significantly at hotter temperatures. These findings show there may be direct negative effects of increasing temperatures on reproductive success and population recruitment, and so hotter temperature during the breeding season may be at least partly responsible for observed population declines. Lastly, I examined genetic structure of populations across mountain ranges separated from one another by lowland habitat unsuitable for Rockjumpers. I predicted I would find little evidence for dispersal between mountain ranges separated by unsuitable lowland habitat, but instead found Rockjumpers show little evidence for inbreeding. I also found evidence for a past bottleneck event or founder effect, and little overall genetic diversity (possibly as their specialized niche exerts selective pressure). Low diversity may limit Rockjumpers' ability to adapt to a changing environment. Adult physiological and behavioural thresholds to increasing temperatures are often used to create predictions of climate change effects. My past physiological research and current behavioural research suggest no particularly strong evidence that temperature-related population declines are driven by poor physiological capacity to tolerate heat or negative behaviour trade-offs. Instead, my current research shows that understanding negative effects of increasing temperatures may require a more in-depth approach involving investigation of fine-scale ecological interactions. No single one of my chapters provides the insight necessary for understanding Rockjumper population declines at warming temperatures. Instead, I show how an integrative approach may be necessary for assessing species' vulnerability to climate change by examining multiple ecological aspects of a single sentinel species, using an alpine species with a narrow thermal range and highly specialized habitat niche.
Keywords: Passeriformes -- South Africa -- Western Cape; Passeriformes -- Physiology -- South Africa -- Western Cape; Passeriformes -- Behavior -- Climatic factors -- South Africa -- Western Cape; Passeriformes -- Reproduction -- Climatic factors -- South Africa -- Western Cape; Passeriformes -- Dispersal -- South Africa -- Western Cape; Passeriformes -- Food -- South Africa -- Western Cape; Passeriformes -- Nests-- -- South Africa -- Western Cape; Blue Hill Nature Reserve; Cape Rockjumper -- Climatic factors; Chaetops frenatus